Dialog filozofii z historią: zagadkowy wstęp do Historii powszechnej Teofilakta Simokatty - Kotłowska, Anna (Vox Patrum, 2018)
The paper seeks to propose an interpretation of Dialogue between History and Philosophy – prefatory to Simocattes’ History. In the author’s opinion, this brief text deprived of literary value, provides for Theophylactus’ peculiar attempt to justify his actions and behavior during the usurpation of Phokas (602-610). Vague mythological metaphors were meant to divert attention from certain biographical facts and to redirect the discussion to the sphere of universal reflections on the rules of power, thereby releasing Theophylactus from potential liability. Therefore, the Dialogue should be understood as a text of an apologetic nature, written from authors’ personal perspective. Such interpretation differs from the few previous ones which, although scarce, have excessively highlighted rhetorical aspects of the text, suggesting even that it has been written at a request of the new government.